PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN ANAK USIA 5-6 TAHUN MELALUI METODE FONIK - Intan Maharani Putri; Taopik Rahman; Qonita (LPPM IAD Probolinggo, 2025)
Basic reading abilities are a crucial component of language development during early childhood. Observations at Amal Sholeh Islamic Kindergarten indicated that a majority of children aged 5 to 6 years experienced challenges in letter recognition, letter pronunciation, and associating sounds with letter symbols as a result of traditional teaching methods. This research seeks to enhance early reading abilities by using phonics techniques that focus on the systematic and multisensory recognition of letter sounds. The research conducted was a Classroom Action Research (CAR) model, based on the framework established by Kemmis and McTaggart, and it was implemented over a period of three months in two distinct cycles. The study involved 17 children who were part of group B. Data were gathered through observation, interviews, and documentation, which were confirmed using technical triangulation and expert assessment, and subsequently analyzed using both qualitative and quantitative methods. The findings revealed an upward trend in each cycle. The capability of teachers in organizing lessons improved from 69. 64% (good) in cycle I to 85. 71% (very good) in cycle II, whereas the execution of learning rose from 73% to 86%. The reading skills of children increased from 32% during the pre-cycle phase to 56. 25% in the first cycle, and further rose to 80% in the second cycle. Consequently, the phonics approach has demonstrated its effectiveness in enhancing reading abilities in young children, while also fostering a more engaging, enjoyable, and meaningful educational experience. Keywords: Early reading; Phonics Method; Letter Recognition